Budget impact analysis of the simplification to atazanavir + ritonavir + lamivudine dual therapy of HIV-positive patients receiving atazanavir-based triple therapies in Italy starting from data of the Atlas-M trial - Restelli U; Fabbiani M; Di Giambenedetto S; Nappi C; Croce D (Dove Medical Press, 2017)
Umberto Restelli,1,2 Massimiliano Fabbiani,3 Simona Di Giambenedetto,3 Carmela Nappi,4 Davide Croce,1,2 1Centre for Research on Health Economics, Social and Health Care Management (CREMS), LIUC – Università Cattaneo, Castellanza, Italy; 2School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 3Institute of Clinical Infectious Diseases, Catholic University of Sacred Heart, 4Health Economics, Bristol-Myers Squibb S.r.l., Rome, Italy Background: This analysis aimed at evaluating the impact of a therapeutic strategy of treatment simplification of atazanavir (ATV)+ ritonavir (r) + lamivudine (3TC) in virologically suppressed patients receiving ATV+r+2 nucleoside reverse transcriptase inhibitors (NRTIs) on the budget of the Italian National Health Service (NHS).Methods: A budget impact model with a 5-year time horizon was developed based on the clinical data of Atlas-M trial at 48 weeks (in terms of percentage of patients experiencing virologic failure and adverse events), from the Italian NHS perspective. A scenario in which the simplification strategy was not considered was compared with three scenarios in which, among a target population of 1,892 patients, different simplification strategies were taken into consideration in terms of percentage of patients simplified on a yearly basis among those eligible for simplification. The costs considered were direct medical costs related to antiretroviral drugs, adverse events management, and monitoring activities.Results: The percentage of patients of the target population receiving ATV+r+3TC varies among the scenarios and is between 18.7% and 46.9% in year 1, increasing up to 56.3% and 84.4% in year 5. The antiretroviral treatment simplification strategy considered would lead to lower costs for the Italian NHS in a 5-year time horizon between –28.7 million € and –16.0 million €, with a reduction of costs between –22.1% (–3.6 million €) and –8.8% (–1.4 million €) in year 1 and up to –39.9% (–6.9 million €) and –26.6% (–4.6 million €) in year 5.Conclusion: The therapy simplification for patients receiving ATV+r+2 NRTIs to ATV+r+3TC at a national level would lead to a reduction of direct medical costs over a 5-year period for the Italian NHS. Keywords: protease inhibitor, economic evaluation, cost, de-intensification, antiretroviral therapy, Italian National Health Service